The Influence of Essential Oils on Gut Microbial Profiles in Pigs - Modestas Ruzauskas; Elena Bartkiene; Arunas Stankevicius; Jurga Bernatoniene; Daiva Zadeike; Vita Lele; Vytaute Starkute; Paulina Zavistanaviciute; Juozas Grigas; Egle Zokaityte; Arnoldas Pautienius; Grazina Juodeikiene; et al. (Animals, 2020)
In recent years, the intake of ultra-processed foods has increased dramatically worldwide. Missing natural foods in the diet raise the need of biologically active food components that could compensate for this deficiency and help maintain proper immune status. This study used pigs as an animal model for the assessment of the impact of consumption of Origanum vulgare plant extract combined with Mentha piperita and Thymus vulgaris essential oils on microbial profile in intestines. A single group of weaned pigs received basal diet, while the other group basal diet supplemented with plant extract and two essential oils in the form of bilayer tablets prepared using “liquid/solid” phase technology. Metagenomic sequencing was performed with the aim to investigate changes of microbial communities in ileum, caecum, and colon. The results demonstrated that the combination of essential oils was non cytotoxic, and had a positive effect on the microbial composition in the large intestine of pigs due to significant increase in the number of probiotic bacteria. The amount of Lactobacillus was 2.5 times and Bifidobacterium 1.9 times higher in the animal group fed with supplement. The combination, however, had some negative impact on the variety of minor species in the distal part of the ileum. Additional studies need to be performed to obtain knowledge on how combinations of essential oils can change bacterial variety in the proximal part of the gastrointestinal tract.